Interviewer BOT Design to Help Student Learning English for Job Interview - Muhammad Junus; Muhammad Sarosa; Martin Fatnuriyah; Mariana Ulfah Hoesny; Zamah Sari (IC-ITECHS, 2014)
To improve skills in English conversation when seeking job in employment interview session is a must to increase competitiveness among other employment seekers. Because of limited resources in our institutions that can help students learning and practice English for interview and achieve their dream work, we design a bot that has personality as an interviewer who asked the questions and then concludes the conversation and make summary of the interview result. This bot interviewer design is using a modern chatter bot named ALICE, and to replicate human intelligent to machine we use AIML. Meanwhile Naive Bayes Algorithm is used to classify the interview result into areas of potentials, talents, and interests of student, and then made a summary in the end of the interview session using a modified phrase reinforcement algorithm where we change the term frequency – inverse document frequency algorithm with Booleanterm frequency using selected keywords. This interviewerbot help student to practice their listening, speaking, know how to answer interviewer questions, and also know their potentials, talents, and area of interests.